A Novel Design Work In Energy Extraction From In-Stream Water By Various Types Of Micro Hydro Turbines - Shahidul, Islam; Syed Shazali, S.T.; Abdullah, Yassin; Sarip, A.S.H. (Publications International Lahore, 2017)
Purpose- Micro-hydroelectricity power projects are becoming popular because it is a proven low cost electricity-generating source. This research designed to evaluate energy extraction efficiency of single stage and multistage blade of micro Hydro turbine. Experiments have been conducted with two-laboratory scale turbine at instream water velocity ranges from 0.5m/s to 1 m/s. The finding shows that energy extraction and transfer efficiency of multistage MHT is about 5.5 percent higher compare to single stage MHT. This study concludes that multistage MHT is cost effective as energy extraction efficiency is higher and it could be an energy solution for rural societies. Indeed, the multistage MHT could be a useful electricity generating equipment for supporting rural economy.